REPRESENTASI FEMINISME DALAM FILM MULAN 2020 - Amarul Akbar; Mulia Ardi (MEDIAKOM : Jurnal Ilmu Komunikasi, 2021)
Films always influence and shape society based on the message of a film. The messages or values that can be in the film can affect the audience cognitively, affectively and conatively. The film Mulan 2020 tells the story of the life of a soldier named Mulan. In this film, female characters are depicted as active narrative objects and carry the message of feminism. The topic of feminism has attracted the attention of researchers because so far women are often portrayed only as passive narrative objects, even the main erotic objects in films. The purpose of this research is to find out the meaning of semiotic code regarding feminism at the level of reality, level of representation and level of ideology. To achieve the objectives of the researcher. The researcher uses a qualitative approach with semiotic analysis based on television codes which are divided into three levels, namely the level of reality, the level of representation and the level of ideology. The results of the study show the values of feminism at the level of reality through the code of appearance, make-up, costumes, speech, environment and behavior. At the level of representation, feminism values are shown through camera codes, characters, actions, conflicts and dialogues. At the ideological level, the values of feminism which are represented by women and nature have a close and inseparable relationship.